Estimation of Consistency of Production of the Pertussis Component of DTP Vaccine in Terms of Immunogenic Activity and Specific Safety Using Shewhart Charts - I. A. Alekseeva; O. V. Perelygina; E. D. Kolyshkina (Биопрепараты: Профилактика, диагностика, лечение, 2018)
WHO experts attribute the resurgence of whooping cough to the wide use of acellular pertussis vaccines (aPs) as components of combination products. In this regard, WHO encourages countries that have not yet switched to the use of aPs to continue to use whole-cell pertussis vaccines (wPs) for primary vaccination. The experience of using pertussis vaccines has shown that companies do not always produce highly efficacious products. The use of statistical methods of samples quality control helps to ensure consistency of the technological process, which results in the production of more homogeneous products, and rules out the possibility of producing low-quality products. This paper presents the results of retrospective evaluation of the consistency of the wP (as a pertussis component of the DTP vaccine) production using Shewhart control charts. It was shown that at some points in time during the analyzed period from January 2017 until March 2018 the technological process of the company lacked proper statistical control. This increased the risk of producing non-uniform and defective products. In order to improve the quality and consistency of pertussis component batches, the company’s quality control and quality assurance services should make extensive use of Shewhart charts on a real-time basis.